The Talaq Phenomenon In The Digital Era: An Analysis Of Divorce Law Through Social Media In The Perspective Of Fiqh And Indonesian Laws - Amrullah, Arfan; Khabib Jamalullail; Mohammad Syaifuddin (Yayasan pendidikan dzurriyatul Quran, 2026)
The phenomenon of divorce (talaq) in the digital era has become an increasingly complex issue alongside the rapid development of communication technology, particularly the use of social media as a medium for pronouncing divorce. This research is significant because it addresses the discrepancy between Islamic jurisprudence, in which some scholars consider talaq via digital media valid if it fulfills the requirements of fiqh, and Indonesian positive law, which mandates that divorce must be carried out through the Religious Court to obtain legal certainty. This study employs a qualitative method with a library research approach, analyzing literature from scholarly journals, books, and relevant legal regulations. The findings indicate that online talaq may result in unregistered divorce without legal recognition, which affects the rights of wives, children, and the family’s administrative status. Moreover, the gap between fiqh and state law creates vulnerabilities to the misuse of digital platforms in family law practices. The study suggests the need for clearer legal regulations, improvement of legal and digital literacy, and stronger collaboration between scholars, academics, and policymakers to address the challenges of digital divorce in Indonesia.